2021
DOI: 10.1177/00219983211031636
|View full text |Cite
|
Sign up to set email alerts
|

Influence of interface ply orientation on delamination growth in composite laminates

Abstract: The standard experimental procedures for determining the interlaminar fracture toughness are designed for delamination propagation in unidirectional specimens. However, in aerospace structural components, delamination usually occurs between plies at different orientations resulting in different damage mechanisms which can increase the value of the fracture toughness as the delamination propagates. Generally, numerical analyses employ the value measured at the delamination onset, leading to conservative results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…One of the main reasons for this discrepancy are the interface properties adopted in the numerical analysis which are obtained from the standard DCB and MMB specimens with a delamination positioned between 0° plies, while in the SSC the skin-stringer separation is positioned between −45° and 45° plies. Previous work [34] has shown that delamination The evolution of the out-of-plane displacements predicted by the numerical model is in agreement with the DIC images from a qualitative point of view. Initially, the global buckling of the specimen starts in the skin with two half-waves on the side of the delamination and three on the opposite (Figure 10a,e).…”
Section: Quasi-static Analysis and Experimental Comparisonsupporting
confidence: 81%
See 2 more Smart Citations
“…One of the main reasons for this discrepancy are the interface properties adopted in the numerical analysis which are obtained from the standard DCB and MMB specimens with a delamination positioned between 0° plies, while in the SSC the skin-stringer separation is positioned between −45° and 45° plies. Previous work [34] has shown that delamination The evolution of the out-of-plane displacements predicted by the numerical model is in agreement with the DIC images from a qualitative point of view. Initially, the global buckling of the specimen starts in the skin with two half-waves on the side of the delamination and three on the opposite (Figure 10a,e).…”
Section: Quasi-static Analysis and Experimental Comparisonsupporting
confidence: 81%
“…One of the main reasons for this discrepancy are the interface properties adopted in the numerical analysis which are obtained from the standard DCB and MMB specimens with a delamination positioned between 0 • plies, while in the SSC the skin-stringer separation is positioned between −45 • and 45 • plies. Previous work [34] has shown that delamination between differently oriented plies results in a large increase of the fracture toughness as the delamination propagates due to the presence of fiber-bridging and delamination migration to adjacent plies, phenomena which were both observed during the performed experimental tests.…”
Section: Quasi-static Analysis and Experimental Comparisonmentioning
confidence: 76%
See 1 more Smart Citation
“…In [ 8 ], resistance against delamination under Mixed-Mode loading (G II = 34%, 85%) was investigated for 0°//0°, 0°//22.5°, 0°//45°, and 0°//90° interfaces. More recent results of similar investigations can be found, e.g., in [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ], and in [ 19 , 20 , 21 , 22 ] where also R-curves were of interest.…”
Section: Introductionmentioning
confidence: 59%
“…25 Moreover, in aerospace structures, delamination usually appears between plies at different orientations. 26 So, the laminates were created by stacking unidirectional plies under the following configurations: 0/90/45, 30/60 and 0/90. For sample manufacturing, the MTM® 57 series resins from the company CYTEC and the standard modulus carbon fiber T700S from the company Toray were used.…”
Section: Materials and Equipmentmentioning
confidence: 99%